The Influence of Different Types of Diabetes on Vascular Complications. (22nd February 2022) - Wei, Jiahua; Tian, Jiaxing; Tang, Cheng; Fang, Xinyi; Miao, Runyu; Wu, Haoran; Wang, Xiuge; Tong, Xiaolin
Abstract : The final outcome of diabetes is chronic complications, of which vascular complications are the most serious, which is the main cause of death for diabetic patients and the direct cause of the increase in the cost of diabetes. Type 1 and type 2 diabetes are the main types of diabetes, and their pathogenesis is completely different. Type 1 diabetes is caused by genetics and immunity to destroy a large number of β cells, and insulin secretion is absolutely insufficient, which is more prone to microvascular complications. Type 2 diabetes is dominated by insulin resistance, leading to atherosclerosis, which is more likely to progress to macrovascular complications. This article explores the pathogenesis of two types of diabetes, analyzes the pathogenesis of different vascular complications, and tries to explain the different trends in the progression of different types of diabetes to vascular complications, in order to better prevent diabetes and its vascular complications.